Reconhecimento de saberes do trabalho e certificação profissional: a experiência da Inglaterra - Natalia Valadares Lima (2015)
This dissertation aims to analyse vocational qualification devices developed by the Government of England, which enable the recognition of knowledge constructed by the subject during the work experience. This study was carried out by means of bibliographical and documentary research, which sought to identify elements in the discourse of the State, the business community, the researchers and workers about the tensions involving the creation of devices of vocational qualification and recognition of knowledge in the country. Whereas the development of mechanisms aiming the recognition of work knowledge cannot be released from discussions on education and vocational training, the research begins with a historical analysis on the development and changes of policies that deal with vocational qualification. It was noted that the collapse of the Taylorism and Fordism models of production, accompanied by the global economic recession that began in 1973, resulted in the growth of State intervention in initiatives in the vocational qualification domain. In this context, Government texts have come to define the form of the provision of education and vocational training programmes at national level, creating programs of training and developing vocational certification devices. The formulation of these devices involved major changes in the organization of vocational training, because, besides enabling the recognition of knowledge of workers, also established the need for development of national evaluation parameters drawn up by employers representatives. Therefore, in a move to centralize the control of the supply and, at the same time, to liberalization of the content, the education and training system in England started to substantiate the notion of competence assessment. To ascertain how the spread of this notion is reflected in the instruments adopted for assessment and recognition of knowledge, we analysed the structure and the content adopted as parameter for certifying wall and floor tilers. With this analyse, it was possible to evidence the appreciation of theoretical and normative knowledge at the expense of the knowledge actually built during the work experience. The most commonly adopted instrument in the process of recognition of knowledge is the portfolio of evidence, which aims to enable the collection of evidence on workers' skills. Finally, we explored the notion of competence adopted in England. This notion is based on assumptions of the Behaviourism and the theory of educational objectives, trying to establish the expected behaviours in each work situation. This disclosure demonstrates the construction of a vocational qualification device that seeks to identify and recognize knowledge from directly observable actions and infer the knowledge involved in the working procedures. Thus, the device of recognition of knowledge and vocational certification in England constitutes an attempt to certify relevant skills for the employers, based on evaluation of criteria defined by them and seeking to form workers suited to market demands.